Makna Simbol Memegang Ketujuh Bintang dan Ketujuh Kaki Dian Emas dalam Wahyu 2:1 dan Refleksi Teologisnya - Yeni Siahaan; Nurelni Limbong; Warserto Freddy Sihombing; Haposan Silalahi; Herdiana Boru Sihombing (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2024)
This research aims to discuss the meaning of the symbol of holding the seven stars and the seven golden candlesticks in Revelation 2:1 and its theological reflection. This research uses a qualitative research method, namely a library research approach. The object studied in this research is the meaning of the symbol of holding the seven stars and the seven golden lampstands. The results and discussion of this research show that the meaning of the symbol of the seven stars is to symbolize the angels/leaders of the congregation and the meaning of the symbol of the seven golden lampstands is to symbolize the congregations that Jesus addresses in Revelation 2:1. This research concludes that the Lord Jesus stated that He held all His angels or messengers, who are currently referred to as shepherds or leaders of the congregation, in the protection of His hands and revealed that Christ never tires of working among His congregation, He wants His congregation to become a shining light, like a lampstand used as a light in the darkness.